2017
DOI: 10.1519/jsc.0000000000001527
|View full text |Cite
|
Sign up to set email alerts
|

Individual Response to Different Forms of Resistance Training in School-Aged Boys

Abstract: Radnor, JM, Lloyd, RS, and Oliver, JL. Individual response to different forms of resistance training in school-aged boys. J Strength Cond Res 31(3): 787-797, 2017-The aim of this study was to examine individual responses to different forms of resistance training on measures of jumping and sprinting performance in school-aged boys. Eighty boys were categorized into 2 maturity groups (pre- or post-peak height velocity [PHV]) and randomly assigned to a plyometric training, resistance training, combined training, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 29 publications
3
79
1
1
Order By: Relevance
“…Again, similar findings were reported by Chaouachi et al (2014) who found that traditional RT provided superior training adaptations compared to both Olympic weight lifting and plyometric training for 5 and 20 meter sprints. However, Radnor et al (2017) reported contradictory results to the present meta-analysis with plyometric training and combined strength and plyometric training providing more positive responders than strength training alone for sprint velocity. The Radnor study incorporated school aged boys (not specifically trained) whereas the present review included both highly trained athletes and untrained youth.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Again, similar findings were reported by Chaouachi et al (2014) who found that traditional RT provided superior training adaptations compared to both Olympic weight lifting and plyometric training for 5 and 20 meter sprints. However, Radnor et al (2017) reported contradictory results to the present meta-analysis with plyometric training and combined strength and plyometric training providing more positive responders than strength training alone for sprint velocity. The Radnor study incorporated school aged boys (not specifically trained) whereas the present review included both highly trained athletes and untrained youth.…”
Section: Discussioncontrasting
confidence: 75%
“…As expected, the combination of plyometrics and RT provided significantly greater improvements in sprint speed and vertical jump height performance than untrained controls with 6 and 12 weeks of training, respectively (Wong et al, 2010; Hopper et al, 2017). Radnor et al (2017) compared 6 weeks of plyometric, RT and combined training and found more positive responders for 30 m sprint speed with the combined pre-PHV group. In the post-PHV group, the combined training provided more positive responders with acceleration (10 m sprint) and squat jumps vs. the plyometric only and RT groups.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is critical in the long term safety of athletes, as previous research has already identified a higher injury rate for individuals around the period of PHV [8,[61][62][63]. Future interventions pursuing sprint and jump improvements should consider eccentric, plyometric and/or other strengthening interventions to supplement their sprint and jumps training to not only increase the performance response, but to provide the technical and physical proficiency required to safely accommodate the physiological changes that occur during this process [25,54,64].…”
Section: The Effects Of Progressive and Traditional Coaching Strategimentioning
confidence: 98%
“…The aim of this study is to build on the findings of previous literature [25] and further inform literature pertaining to within-PHV characteristics. This study will utilise two different coaching approaches (traditional and progressive) to identify the most effective strategy to improve sprint and jump performance within pre, circa and post-PHV maturation groups.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that a combination of high force and high velocity exercises is superior to one or the other exclusively (33) and can successfully be performed within the same training sessions to develop a range of fitness qualities (53,75). The range of exercise intensities and velocities in mesocycles 7 and 8 reinforces this mixed method (high-force and high-velocity movements) approach advocated by Haff and Nimphius (25); 1-5 sets of 2-8 reps was used to allow for higher loading and more interset recovery.…”
Section: Macrocyclementioning
confidence: 99%